The good, the bad and the ugly [videorecording (DVD)] - Leone, Sergio, 1929-1989; Eastwood, Clint, 1930-; Van Cleef, Lee, 1925-1989; Wallach, Eli, 1915-2014 (KL studio classics., 2017)
The inimitable "Man with no name" teams with two gunslingers to pursue a fortune in stolen gold, but they soon discover their greatest challenge is to stay alive.